Approach to strategy and enterprise size = Charakter realizowanej strategii w przedsiębiorstwach różnej wielkości - Radomska, Joanna (Zielona Góra: Faculty of Economics and Management Press)
The article describes the subject of approach to strategy based on the current classification differentiating five types of approach specified on the basis of three features relating to business environment, such as predictability (ability to forecast), malleability (ability to shape) and harshness (ability to survive). The research demonstrated the existence of a correlation between the approaches and the size of an enterprise, indicating that small organisations most often apply a classical and renewal strategy.
Keywords: podejście do strategii; rozmiar przedsiębiorstwa; strategia; approach to strategy; size of the company; strategy